High Lithium Storage Performance of FeS Nanodots in Porous Graphitic Carbon Nanowires. (2nd March 2015) - Zhu, Changbao; Wen, Yuren; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Much attention has been paid to increase the energy density of Li‐ion batteries, in order to fulfill the requirements of electric vehicles and grid‐scale energy storage. While for anodes various options are available, this is not at all the case for cathodes. In this context, the inexpensive and environmentally benign iron sulfides have been investigated as cathode materials due to the remarkably high capacity based on the conversion reaction. Here, the preparation of FeS nanodots accommodated in porous graphitic carbon nanowires is reported via a combination of electrospinning technique and biomolecular‐assisted hydrothermal method. These materials exhibit excellent electrochemical performances also as cathode materials, with energy densities even higher than the current LiCoO2 intercalation cathode. Moreover, key problems of conversion reaction, such as the low degree of reversibility, large polarization are far‐reachingly mitigated. Abstract : FeS nanodots accommodated in porous graphitic carbon nanowires are obtained via the combination of electrospinning technique and a biomolecular‐assisted hydrothermal method. These materials exhibit excellent electrochemical performances as cathode materials. Key problems of conversion reaction, such as the low degree of reversibility and large polarization, are far‐reachingly mitigated.